Road traffic accidents and its determinants among Kenyan households: analysis of the 2022 national health survey using multilevel modeling - Bewuketu Terefe; Mahlet Moges Jembere; Bikis Liyew (BMC Public Health)
Abstract Background The incidence of road traffic accidents, which have been widely identified as a significant public health issue worldwide, is higher in low- and middle-income nations such as Kenya than in high-income nations. However, there is a dearth of national data regarding the epidemiology of road traffic accidents in Kenya. This study used data from a recent national survey to determine the prevalence and associated factors of road traffic accidents among household members in Kenya. Methods Data from the recent Kenyan demographic and health survey completed in 2022 were evaluated in this study. A weighted sample of 145,880 household members provided the data. Enumeration areas served as the primary sampling units, and households served as the secondary sampling units in a stratified two-stage cluster sampling procedure. Key causes of road traffic accidents in Kenya were investigated using univariate and multivariable multilevel logistic regressions. To ascertain if variables were statistically significant in the final model for the bivariate analysis and multivariable multilevel regression, P values of ≤ 0.2 and < 0.05 were used, respectively. Results The prevalence of road traffic accidents was determined to be 6.33% (95% CI = 0.32–12.07). As compared to households with young and adolescent members, those whose age was from 25 to 34 years (AOR = 1.20, 95% CI = 1.03,1.39), middle wealth index (AOR = 1.08, 95% CI = 1.01,1.16), primary (AOR = 1.12, 95% CI = 1.05,1.19), and secondary/higher education (AOR = 1.14,95% 1.06,1.22), smokers (AOR = 1.31, 95% CI = 1.22,1.41), exposed for radio (AOR = 0.92, 95% CI = 0.87,0.97), being female (AOR = 0.72, 95% CI = 0.68,0.76), and coming from higher educated communities (AOR = 1.67,95% CI = 1.35,2.08) more times to be exposed for road traffic accidents as compared to their counterparts, respectively. Conclusions The prevalence of road traffic accidents in Kenyan household members was considerably lower when compared to other preceding findings. To reduce or stop the occurrence in Kenya, however, policymakers, implementors, and other concerned authorities should concentrate on the highlighted variables.